2000
DOI: 10.1002/1529-0131(200002)43:2<414::aid-anr23>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of systemic vasculitis: A ten-year study in the United Kingdom

Abstract: In our study population, the annual incidence of PSV is slowly increasing with time and the incidence is greatest in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
205
5
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(241 citation statements)
references
References 15 publications
15
205
5
16
Order By: Relevance
“…In our population, ANCA and AAV were present in 11% and 4%, respectively, of patients treated with antithyroid drugs. Prevalence of primary systemic vasculitis (Wegener's granulomatosis, microscopic polyangiitis, Churg-Strauss syndrome, polyarteritis nodosa) has been estimated at 144.5/million (0.01%) in a population comparable with the general population in Groningen (30). Therefore, a prevalence of AAV of 4% in our patients treated with antithyroid drugs clearly suggests a relationship between these drugs and the presence of AAV.…”
Section: Discussionmentioning
confidence: 57%
“…In our population, ANCA and AAV were present in 11% and 4%, respectively, of patients treated with antithyroid drugs. Prevalence of primary systemic vasculitis (Wegener's granulomatosis, microscopic polyangiitis, Churg-Strauss syndrome, polyarteritis nodosa) has been estimated at 144.5/million (0.01%) in a population comparable with the general population in Groningen (30). Therefore, a prevalence of AAV of 4% in our patients treated with antithyroid drugs clearly suggests a relationship between these drugs and the presence of AAV.…”
Section: Discussionmentioning
confidence: 57%
“…In the 1980s, the incidence of AASV was 10 per 10 6 in the United Kingdom, but after ANCA were clinically available in the 1990s, the incidence of AASV increased to 20 per 10 6 in the United Kingdom (4,11,12,13,15). The incidence of AASV in the Chinese population is unknown.…”
Section: Discussionmentioning
confidence: 91%
“…The first difference concerned sexual predominance. Many reports revealed that Caucasian patients were male predominant (12,13), while for the Chinese patients, males and females are equally affected; however, for the Chinese patients under 20 years of age, the females are clearly predominant (4:1), a finding that needs to be further studied. The second concerned antigenic predominance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from England, Spain, and Scandinavia have shown that the overall annual incidence of primary systemic vasculitis is approximately 20 cases per million (42)(43)(44). In various populations, certain types of vasculitis appear more frequently, suggesting that either genetic or environmental factors may be associated with the prevalence of vasculitis in certain populations.…”
Section: Discussionmentioning
confidence: 99%